Trends of Trade Deficit and its impact in Nepalese Economy with ARDL Approach: Some Suggestive Measures to Overcome (Orchid Academia Siraha, 2024)
Nepal's ongoing trade imbalance has been a major obstacle to the country's economic stability and expansion. This paper employs the ARDL approach to analyze the trends and impacts on trade deficit of Nepalese economy. The ARDL analysis highlights the adverse impacts of the trade deficit on key economic indicators, underscoring the urgency of implementing effective policy measures. Nepal can endeavor to lower its trade deficit and achieve sustainable economic growth in order to combat poverty by implementing the recommended steps. The imported Foreign aid, foreign direct investment in Nepal is high and this also lead trade deficit. The trends of import are gradually increasing by 4.87 times and export increasing by 1.42 times.